VACCINATION WITH VIBRIO ANGUILLARUM AND VIBRIO ORDALII BACTERINSAGAINST VIBRIOSIS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
key words:Vaccination with vibrio Anguillarum - Vibrio ordalii bacterins against vibriosis